VERGİ HUKUKUNDA ZAMANAŞIMI SÜRESİNİN BAZI DURUMLARDA UZAMASI HALİNDE DEFTER VE BELGELERİN MUHAFAZA VE İBRAZ DURUMU - (:unkn) unknown (My University, 2015)
Vergi hukukunda zamanaşımı, verginin tarh, tahakkuk ve tahsil aşamalarında titizlikle nazara alınması gereken önemli bir müessesedir. Bu sadece vergi güvenliği için değil, aynı zamanda vergicilikte adil olma prensibinin bir gereği olarak, mükellef hukuku bakımından düşünülmesi ve objektif olarak uygulanması gereken bir husustur. Bugün ekonominin hızlı değişimler içerisinde olması, vergilerle ilgili olarak sürekli düzenlemelerin yapılması, siyasi etkiler, vergisel işlemlerin uluslararası boyutu gibi nedenlerden dolayı vergi sistemimiz oldukça karmaşık bir yapıya bürünmüş ve uygulamada bir takım sorunları karşımıza çıkartmıştır. Bu doğrultuda çalışmamızda, zamanaşımı süresinin bazı durumlarda uzaması halinde defter ve belgelerin muhafaza ve ibraz durumu esas alınmıştır. Önemli görülen hususlar öğretide yer verilen öneriler doğrultusunda incelenmiştir.

Prescription in tax law, the imposition of tax, assessment and collection stages is an important institution that should be taken into account carefully. This is not only for the safety of taxes. This is not only for the safety of taxes, but also as a requirement of the principle of fairness in taxation is an issue that should be applied objectively and to be considered taxpayer in terms of law. Today, due to reasons such as, we have a complex structure of the economy, the introduction of new taxes, political effects, the international dimension of the tax transactions, our tax system is a clad highly complex a structure and a number of problems have been encountered in practice. Therefore, in 15 * Marmara Üniversitesi, İktisat Fakültesi, Maliye Bölümü, fatma.turna@marmara.edu.tr** our study, in some cases, if the extension of the prescription period, proof are based on the preservation and presentation problem. For the issue in question by examining the suggestions contained in the doctrine has been evaluated in accordance with our review.
THE PRODUCTION OF BOOKS AND DOCUMENTS IN CASE OF EXTENSİON OF THE PRESCRİPTİON PERİOD IN TAX LAW
Keywords: İktisat; İşletme